Indikasi Praktik Penetapan Harga Predatori di Marketplace Online dari Perspektif Hukum Persaingan Usaha - Prastika, Danisha Rahmadanty; Wulandari, Sinar Aju (Fakultas Hukum Universitas Hang Tuah, 2026)
This research examines the impact of predatory pricing practices on unfair competition in Indonesia, particularly in the context of the rapidly growing ecommerce sector. With the emergence of the “live shopping” feature, sellers can offer products directly to consumers, creating a more dynamic interaction and urgency to make purchases. However, this aggressive pricing strategy has the potential to disrupt market equilibrium, as the prices set often do not reflect actual production costs, thereby threatening the principle of healthy competition that should arise from the natural supply and demand mechanism. This type of research is legal research that addresses existing legal issues by identifying legal problems, legal reasoning, and analyzing existing legal issues, as well as providing solutions to the legal problems faced. The problem-solving approach used in this research is the statute approach and case study. This research also highlights the risks faced by consumers, who may have to pay higher prices after competitors exit the market, and the risk of unhealthy competition and the creation of monopolies or oligopolies that hinder innovation as a result of predatory pricing. Therefore, it is important to evaluate existing regulations and ensure that predatory pricing practices do not harm businesses and consumers in Indonesia.